2018
DOI: 10.1111/pim.12596
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of alveolar echinococcosis via PD‐1/PD‐L1 immune checkpoint blockade in mice

Abstract: Summary The growth potential of the tumour‐like Echinococcus multilocularis metacestode (causing alveolar echinococcosis, AE ) is directly dependent upon the nature/function of the periparasitic adaptive host immune‐mediated processes. PD ‐1/ PD ‐L1 pathway (programmed cell death 1), which inhibits lymphocytic proliferation in tumour development, is over‐expressed at the chronic stage of AE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 48 publications
(56 reference statements)
2
54
0
Order By: Relevance
“…Such observations are consistent with the effect of TIGIT on the generation of mature immunoregulatory dendritic cells; its role on the inhibition of TNF‐α secretion is also consistent with the dramatic effect of TNF gene deletion shown on E. multilocularis infection susceptibility in mice . Our results are also in line with observations that anti‐PD‐L1 mAb or recombinant EmP29 antigen administration result in a change of Treg and/or T h 2/T h 1 ratio, which may be responsible for partial restriction of metacestode growth . However, in most studies, positive results of immunotherapy were observed when the biotherapeutic agent was administered at time of infection, thus preventing the establishment of the metacestode, which is not applicable to the clinical situation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Such observations are consistent with the effect of TIGIT on the generation of mature immunoregulatory dendritic cells; its role on the inhibition of TNF‐α secretion is also consistent with the dramatic effect of TNF gene deletion shown on E. multilocularis infection susceptibility in mice . Our results are also in line with observations that anti‐PD‐L1 mAb or recombinant EmP29 antigen administration result in a change of Treg and/or T h 2/T h 1 ratio, which may be responsible for partial restriction of metacestode growth . However, in most studies, positive results of immunotherapy were observed when the biotherapeutic agent was administered at time of infection, thus preventing the establishment of the metacestode, which is not applicable to the clinical situation.…”
Section: Discussionsupporting
confidence: 91%
“…Persistence of E. multilocularis is associated with a chronic granulomatous inflammation, leading to the disruption of the normal function of T cells, which is nowadays referred to as “functional exhaustion.” Recent reports have also shown that E. multilocularis infection is associated with the expression of “checkpoint” receptors that are known to limit the activity of parasite‐specific lymphocytes. We and others have shown that the receptors programmed cell‐death 1 (PDCD1), 2B4 (SLAMf4, CD244), and lymphocyte‐activation gene 3 (LAG3) are aberrantly expressed during chronic infection, and that they contribute to “exhausted” parasite‐induced T‐cell response and lead to the maintenance of E. multilocularis survival . Observations in humans and experimental studies in animals suggest that, in the absence of fully effective antiparasitic chemotherapy for AE, modulation of the host immune response, specifically, blocking the coinhibitory receptors (e.g., PDCD1), could be envisaged to fight against the parasite and to prevent the disease and/or its complications.…”
mentioning
confidence: 99%
See 3 more Smart Citations